Hair cortisol concentrations were not impacted by collection region in cross-bred Angus steers - Loh, H. Y.; Okoren, C.; Velazco_Marroquin, David; Keogh, L.; Coetzee, J.; Edwards-Callaway, L. N.; Engle, T. E.; Cramer, M. C. (Frontiers in Animal Science, 2025)
Hair cortisol has been used to evaluate long-term stress in cattle. However, hair sample collection regions vary between studies. The objective of this experiment was to evaluate hair cortisol concentrations in four different anatomical locations on cattle to determine if cortisol concentrations differed between sampling regions or sides. Sixteen crossbred black Angus steers (≥ 24 months of age, 800 ± 10 kg) were utilized in this experiment. Hair samples were collected from 1) left hip, 2) left shoulder, 3) right hip, and 4) right shoulder of each steer (4 samples/animal). Hair samples were analyzed for cortisol using an ELISA kit. A linear mixed effect model and type III analysis of variance were fitted for statistical analysis using R software, with steer being the whole plots and location of hair collection being the split plots. Hair cortisol concentration was similar (P > 0.10) across different collection regions. However, the study had a lower statistical power and therefore results should be interpreted cautiously. Hair cortisol analysis is a useful tool to evaluate long-term stress in animals; understanding the consistency of hair cortisol concentrations between body regions can influence how sample collection occurs in future studies. The current study indicated that hair sampled from left hip, left shoulder, right hip, and right shoulder of the cattle have similar hair cortisol levels under these conditions. The present study was limited by sample size, and more studies that assess variations in hair cortisol to due sampling location, age, and breed are needed.